P147 Are video recordings of consultations in HIV and genitourinary medicine (GUM) acceptable to patients and staff?. (23rd May 2012) - Daniel, B; Cohen, C E; Day, S; Mandalia, S; Theobald, N J
Abstract : Background: Video recordings of consultations (VC) are used in general practice to improve junior doctors' training, having been shown to be acceptable to patients. Aims: To determine the acceptability of VC in GUM/HIV, excluding physical examinations. Methods: After identifying potential VC concerns from a pilot study, patient surveys were distributed within GUM/HIV clinics September 2010–May 2011. Staff (ST) surveys were distributed electronically and via post October 2011–January 2012. Both included questions on confidentiality, videotape storage, potential impact on the patient-clinician interaction and additional time incurred. Results: Of 1171 patient questionnaires distributed, 1002 (86%) were returned; 57% (570) were GUM and 43% (432) HIV clinic attendees; 86% (860) aged 20–49 years. Two–thirds (659) were male, of whom 77% (507) were men who have sex with men. Nearly half (47%) considered VC acceptable. After adjustment for other factors, multivariate analysis showed non-acceptability was independently associated with concerns re confidentiality RR 10.7 (95% CI 6.5 to 17.5, p<0.001) and with not wanting the consultation to take two extra minutes RR 17.2 (95% CI 9.3 to 31.9, p<0.001). ST surveys were distributed to 140 members; 31% (44) returned. Of note, distribution coincided with introduction of a new coding system. In total, 34% (15) were nurses, 25% (11) consultants/associate specialists, 18% (8) ST/trust grades, 14% (6) trainee doctors, 9% (4) other. Two-thirds (29) were female. Of all ST, 73% (32) found VC acceptable. Univariate analysis did not show any possible cause for likelihood of non-acceptability. Conclusion: Nearly half our patients thought VC acceptable, with concerns cited around confidentiality and time, compared to nearly three quarters of ST. ST survey uptake was low, perhaps due to the time constraints noted above. Once the specific patient concerns have been addressed, VC could be introduced in GUM/HIV as a valuable educational tool for all clinical ST.